Duties of Directors and Controlling Shareholders in Relation to Share-Trading. - Barnes, Kiser Dave (Obafemi Awolowo University, 2014)
For nearly a score years the threatened or actual creation, allotment, and issue of company shares by its board of directors have provided the factual background for the leading cases on directors’ fiduciary duty to exercise management powers over shares for a proper corporate purpose.